2019
DOI: 10.1002/pmrj.12167
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity Modifications Following a Lower‐Limb Amputation: A Systematic Review

Abstract: Background: Although there are studies that have examined brain functional reorganization following upper-limb amputation, understanding of the brain changes that occur in people with lower-limb amputation is limited. Objective: To investigate modifications in the brain following lower-limb amputation. Methods: We included case-control studies that evaluate neuroplasticity in the central nervous system using neuroimaging techniques. A literature search was conducted using MEDLINE, CINAHL, Web of Science, Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
2
20
0
1
Order By: Relevance
“…Through seed-based whole-brain FC calculations we found that IPL_R and SPG_R regions in ULAs exhibit decreased functional connections with many areas throughout the brain, including lingual area, precentral area, frontal area, insula area, among others ( Figures 4 , 5 ). Related studies on post-amputation changes corroborate our finding that remodeling of brain function is not limited only to local sensorimotor areas in the brain that represent the respective limb ( Makin et al, 2015 ; Zhang et al, 2018 ; Molina-Rueda et al, 2019 ). How might these widespread changes be manifest behaviorally?…”
Section: Discussionsupporting
confidence: 85%
“…Through seed-based whole-brain FC calculations we found that IPL_R and SPG_R regions in ULAs exhibit decreased functional connections with many areas throughout the brain, including lingual area, precentral area, frontal area, insula area, among others ( Figures 4 , 5 ). Related studies on post-amputation changes corroborate our finding that remodeling of brain function is not limited only to local sensorimotor areas in the brain that represent the respective limb ( Makin et al, 2015 ; Zhang et al, 2018 ; Molina-Rueda et al, 2019 ). How might these widespread changes be manifest behaviorally?…”
Section: Discussionsupporting
confidence: 85%
“…Recently however, studies have focussed on the kinetics and muscular activity of amputee gait to provide a more complete picture of the biomechanics of the limbs and trunk during amputee walking. Studies assessing the effect of different prosthetic components [6][7][8] and of amputation level [9][10][11][12][13][14] during amputee gait have led to consistent findings of reduced peak ankle plantar-flexion moment and power and increased peak hip power generation and absorption in amputees. This has led to several avenues of research, particularly the design and development of active (powered) prosthetic limbs [15][16][17].…”
mentioning
confidence: 92%
“…An efficient gait will likely be dependent on energy conserving exchanges between limb segments and also on energy storage and return mechanisms, typically utilising strain energy in tendons and prosthetic components. In unilateral amputees, it is known that the intact limb often compensates for deficiencies on the prosthetic side, which leads to characteristic gait asymmetries of reduced stance time and increased swing time and step length on the prosthetic side [10,11]. However, despite these asymmetries, fit individuals with a trans-tibial amputation as a result of trauma often have a metabolic cost of walking that is close to that of healthy able-bodied controls [4,18], suggesting that, in certain cases at least, it is possible to overcome the deficiencies associated with the loss of limb.…”
mentioning
confidence: 99%
“…For example, one resting-state electroencephalogram (EEG) study showed that changes in the neural network of patients with right-sided amputations weakened the inhibitory effect of the sensorimotor area, and that connectivity of the right parietal lobe area increased ( Lyu et al, 2016 ). Moreover, recent studies have shown that amputees have structural and functional changes to multiple brain areas, such as the premotor cortex, and the supplementary motor area ( Molina-Rueda et al, 2019 ). These structural and functional changes can be interpreted as non-adaptive brain remodeling due to sensory deprivation and loss or decreased autonomous control ability ( MacIver et al, 2008 ; Raffin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%